Emission Trading Systems and the Optimal Technology Mix - Gregor Zöttl (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
Cap and trade mechanisms enjoy increasing importance in environmental legislation worldwide. The most prominent example is probably given by the European Union Emission Trading System (EU ETS) designed to limit emissions of greenhouse gases, several other countries already have or are planning the introduction of such systems. One of the important aspects of designing cap and trade mechanisms is the possibility of competition authorities to grant emission permits for free. Free allocation of permits which is based on past output or past emissions can lead to inefficient production decisions of firms' (compare for example Bohringer and Lange (2005), Rosendahl (2007), Mackenzie et al. (2008), Harstad and Eskeland (2010)). Current cap and trade systems grant free allocations based on installed production facilities, which lead to a distortion of firms' investment incentives, however. It is the purpose of the present article to study the impact of a cap and trade mechanism on firms' investment and production decisions and to analyze the optimal design of emission trading systems in such an environment.
urn:nbn:de:bvb:19-epub-12151-3
Keywords: H21; H23; Q55; 330; Emissions Trading; Free Allocation; Investment Incentives; Technology Mix; Emissionshandel; Preis; Anreizregulierung; Emissionshandel; Investition; Technologiewahl; Ökonomischer Anreiz; Theorie